Humans as “Part and Parcel of Nature”: Thoreau’s Contribution to Environmental Ethics - Matzke, Jason P. (ETHICS IN PROGRESS, 2014)
Henry David Thoreau (1817-1862) develops an understanding of human beings as “part and parcel of nature” that includes the idea that we are physically, spiritually, and attitudinally (more or less) connected to the world around us. The image he offers is one in which life spent too much in civilization, where work and social expectations determine the quality of one’s daily life and personal character, lead to lives of boredom, conformity, and misplaced priorities. Time spent in more natural environments is the antidote. Such experiences have the potential to jar us out of the conformist and—to his mind—personally stunting existence into which most fall. Growth and liberation come from experiencing the “More” of which both nature and we are a part. Thoreau calls us to reevaluate our values and priorities by being in a right relationship with nature, which does not require that we accept all of his particular ontological commitments. The argument that emerges for greater protection of the environment is admittedly quite human-centered. However, Thoreau’s insight that we are part and parcel of nature is important because, as Aldo Leopold later argues, we can only progress beyond a prudential approach to nature when we see ourselves as part of the larger whole. The world looks different when it is our home and community as opposed to being mere material to be used or a stage on which our lives unfold.